Effectiveness of realistic mathematics education: A meta-analysis - Akosah, Ernest Frimpong; Dissou Arthur , Arthur; Adu Obeng, Benjamin (American Journal of STEM Education, 2026)
This study uses a meta-analysis of 15 studies (2014–2023) to assess the effectiveness of the Realistic Mathematics Education (RME) approach in improving students’ mathematics achievement. RME, which emphasizes real-life contexts and student-centered learning, showed a significant overall effect size (Hedges’ g = 0.65). Despite variability across studies, no major publication bias was detected, and consistent positive impacts were observed. The findings support the integration of RME into curricula, particularly in regions with persistent underperformance in mathematics. The study recommends improved teacher training, development of RME-based materials, and wider adoption of RME, along with further research into its long-term and cross-cultural impact.